2014
DOI: 10.1002/chem.201403724
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Free Synthesis and Mechanistic Study of Porous Three‐Dimensional Hierarchical Uranium‐Containing and Uranium Oxide Microspheres

Abstract: A novel type of uranium-containing microspheres with an urchin-like hierarchical nano/microstructure has been successfully synthesized by a facile template-free hydrothermal method with uranyl nitrate hexahydrate, urea, and glycerol as the uranium source, precipitating agent, and shape-controlling agent, respectively. The as-synthesized microspheres were usually a few micrometers in size and porous inside, and their shells were composed of nanoscale rod-shaped crystals. The growth mechanism of the hydrothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
(16 reference statements)
0
14
1
Order By: Relevance
“…Indeed, Balice et al first separated the initial oxalate precipitate from the supernatant then poured it into a mixture of deionized water and hydrazine to perform their final conversion. The concentrations of organic species in the reacting media, which were frequently depicted as shaping agents, were then lower than that obtained in this work. Consequently, the aggregation of the nanocrystallites was most probably disadvantaged.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Indeed, Balice et al first separated the initial oxalate precipitate from the supernatant then poured it into a mixture of deionized water and hydrazine to perform their final conversion. The concentrations of organic species in the reacting media, which were frequently depicted as shaping agents, were then lower than that obtained in this work. Consequently, the aggregation of the nanocrystallites was most probably disadvantaged.…”
Section: Resultscontrasting
confidence: 80%
“…Simultaneously, actinides are hydrolyzed to form hydroxo- or oxohydroxo- species that finally age into oxides . Some authors reported on the formation of spherical particles at the microscopic scale using aspartic acid or urea as complexing agents, and the use of oxalates was mostly related to the preparation of nanometric particles . Also, the studies frequently focused on the morphology of the powders obtained and generally lacked a complete chemical characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this kind of process requires specific equipment, which might be difficult to implement in nuclear facilities aiming to work with radionuclides of high specific activity. On this basis, simple wet-chemistry routes based on the hydrothermal precipitation of mixtures containing either thorium, uranium(IV) or uranium(VI) in acidic solutions, precipitating agent (urea) and shaping agent (PEG, glycerol) were recently considered [16][17][18] This study reports a new and simple wet chemistry route to spherical UO 2 particles from the initial precipitation of uranium(IV) aspartate and its conversion under hydrothermal conditions. Aspartic acid was chosen as precipitating agent owing to its good complexation properties with regard to actinides 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…of thorium incorporation, SEM observations revealed a drastic decrease of the microparticles size, which appeared to be typically between 50 and 250 nm in diameter. As the formation of microspheres was assigned to the self-assembly of elementary nanometric crystallites thanks to the adsorption of residual organic species [48], it is most likely that the incorporation of thorium in the samples modifies the surface chemistry of the crystallites, and precludes the formation of larger assemblies. Nevertheless, owing to the compositions targeted in the field of nuclear safeguards (typically lower than 1 mol.%), this does not appears as a limitation.…”
Section: Iii1 Effect Of Thorium Doping On Raw Particles Structure/mic...mentioning
confidence: 99%